Friendship Support and Academic Motivation in First-Generation University Students: Academic Anxiety as a Moderator and Sense of Belonging as a Mediator - Mtshweni, Bongani V (Bulletin of Counseling and Psychotherapy, 2025)
In this study, the influence of friendship support on academic motivation with academic anxiety as a moderator and sense of belonging as a mediator was investigated. A cross-sectional quantitative research design was used, with a convenient sample of 240 undergraduate first-generation students (FGS) from a South African university. Data were collected using an online questionnaire comprising four instruments: The Multidimensional Scale of Perceived Social Support (MSPSS), Psychological Sense of School Membership (PSSM), Anxiety Scale for Undergraduate Students (ASUS) and Academic Motivation Scale (AMS). The simple linear regression analysis results showed that friendship support significantly predicted academic motivation. In addition, the moderation analysis results revealed that academic anxiety did not significantly moderate the relationship between friendship support and sense of belonging. Moreover, the mediation analysis results demonstrated that sense of belonging did not significantly mediate the relationship between friendship support and academic motivation. The findings of the study highlight that FGS should strive to cultivate supportive friendships and enhance feelings of belonging towards their institution to mitigate the adverse effects of academic anxiety and bolster their academic motivation for study success.